Designing an assessment system of buildings for all lifecycle stages based on the concept of eco-efficiency - Takashi , Akimoto (2008)

(untitled)
CASBEE (Comprehensive Assessment System for Building Environmental Efficiency) is an environmental labeling method for buildings, based on assessment of the environmental performance of buildings. In CASBEE, BEE (Building Environmental Efficiency) was developed as a new indicator for assessment following the concept of eco-efficiency. With the increasing BEE value, the total environmental performance of buildings is labeled from the highest performance. The framework of basic and extended CASBEE tools as a structured assessment system is called the “CASBEE family”. CASBEE consists of a set of four basic assessment tools, namely “CASBEE for Pre-design” (CASBEE-PD), “CASBEE for New Construction” (CASBEE-NC), “CASBEE for Existing Building” (CASBEE-EB) and “CASBEE for Renovation” (CASBEE-RN). These correspond to the individual stages of the building's lifecycle. There are also needs for detailed assessment targeting specific environmental aspects. “CASBEE-HI,” as an extended tool, assesses efforts made in buildings to alleviate the heat island effect. A new tool called “CASBEE for Urban Development” (CASBEE-UD) is developed for assessment of a group of buildings. In Japan, approximately 500,000 detached houses are constructed every year. In order to improve the quality of houses, “CASBEE for Home” was introduced in 2007. Some local authorities introduced CASBEE into their building administration as assessment methods for their sustainable building reporting systems. This requires building owners to submit a planning document assessing the environmental performance of their buildings to the authorities. In April 2004, the city of Nagoya introduced “CASBEE Nagoya”. Introduction of CASBEE followed in the city of Osaka, Yokohama, Kyoto, and other municipals. These local systems require some modification in CASBEE to reflect their local characteristics, such as climate and prioritized policies.